2022
DOI: 10.1021/acsomega.2c03560
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Modules: Design Optimization

Abstract: The increasing demand for solar energy has led researchers worldwide to develop new photovoltaic technologies. Among these, perovskite materials are one of the most promising candidates, with a performance evolution unparalleled in the photovoltaic field. However, this thin-film technology is not yet available at a commercial level, mainly due to upscaling issues. This work studied the best design options for upscaling single cells into modules by minimizing electrical losses in the device substrates. The soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For homology-based prediction, firstly, protein repertoires of H. glycines (GCA_004148225.2) 41 , G. pallida (GCA_000724045.1) 42 , G. rostochiensis (GCA_900079975.1) 43 , M. incognita (GCA_900182535.1) 44 , M. hapla (GCA_000172435.1) 45 , Caenorhabditis elegans (GCA_000002985.3) 46 , Haemonchus contortus (GCA_000442195.1) 47 , Pristionchus pacificus (GCA_918442795.1) 48 , Brugia malayi (GCA_000002995.5) 49 , Drosophila melanogaster (GCA_029775095.1) 50 and Homo sapiens (GCA_024586135.1) 51 were aligned against the H. filipjevi genome using TBLASTN (Version 2.2.29) 52 . Secondly, the BLAST hits were conjoined by Solar software (version 0.9.6) 53 . Thirdly, GeneWise (version 2.2.0) 54 was used to predict the exact gene structure of the corresponding genomic region on each BLAST hit.…”
Section: Methodsmentioning
confidence: 99%
“…For homology-based prediction, firstly, protein repertoires of H. glycines (GCA_004148225.2) 41 , G. pallida (GCA_000724045.1) 42 , G. rostochiensis (GCA_900079975.1) 43 , M. incognita (GCA_900182535.1) 44 , M. hapla (GCA_000172435.1) 45 , Caenorhabditis elegans (GCA_000002985.3) 46 , Haemonchus contortus (GCA_000442195.1) 47 , Pristionchus pacificus (GCA_918442795.1) 48 , Brugia malayi (GCA_000002995.5) 49 , Drosophila melanogaster (GCA_029775095.1) 50 and Homo sapiens (GCA_024586135.1) 51 were aligned against the H. filipjevi genome using TBLASTN (Version 2.2.29) 52 . Secondly, the BLAST hits were conjoined by Solar software (version 0.9.6) 53 . Thirdly, GeneWise (version 2.2.0) 54 was used to predict the exact gene structure of the corresponding genomic region on each BLAST hit.…”
Section: Methodsmentioning
confidence: 99%
“…So far, previous studies have reported various coating methods for large-area modules, [4][5][6][7][8][9][10][11][12][13][14] proper module designs, [15,16] and interconnection methods. [4,[17][18][19][20][21][22] Also, monolithic interconnection plays a critical role in solar module performance, and therefore, interconnection methods such as mechanical scribing and laser scribing have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Module interconnection was established as a serial connection using laser scribing and executed through P1, P2, and P3. [23,24] P1 and P3 separate adjacent cells by removing the bottom and top electrodes, respectively, and P2 exposes the bottom electrode to connect the top and bottom electrodes when the top-electrode material is deposited. The laser-scribing quality significantly Although the efficiency of hybrid lead-halide perovskite solar cells has been significantly improved, the efficiency gap between small-area cells and large modules continues to be a considerable challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing dead area, adapting to flexible substrates, and integrating architecture play crucial roles in scaling up single cells into large and efficient modules, efficiently. [ 30 ] Commonly, PSCs have been fabricated on the transparent conductive oxides (TCO) with sheet resistance of ≈10 Ω sq −1 . [ 31 ] Unfortunately, the sheet resistance of TCO increases at large scales, resulting in enhanced current losses in the solar cell.…”
Section: Introductionmentioning
confidence: 99%